Bioadhesive chitosan hydrogel with dynamic covalent bonds and sustained kartogenin release for endogenous cartilage regeneration - Li, Mingjing; Li, Fan; Xu, Jian; Zhu, Li; Xiang, Jiang; Zhu, Chunquan; Dai, Zonghui; Tang, Sen; Ouyang, Fucheng; Yu, Jiawen; Huang, Xinwei (Frontiers in Bioengineering and Biotechnology, 2025)
Articular cartilage defects are clinically prevalent yet lack effective therapeutic solutions. Recent advancements in acellular cartilage tissue engineering combined with microfracture techniques have shown promising outcomes. Injectable hydrogels have emerged as particularly attractive scaffolds due to their minimally invasive implantation and capacity to conform to irregular cartilage defects. However, their clinical application remains constrained by inadequate mechanical strength and insufficient bioadhesion. In this study, we developed a bioadhesive dynamic hydrogel by integrating catechol-functionalized chitosan with aldehyde-terminated four-arm polyethylene glycol (AF-PEG). When combined with KGN-loaded PLGA/PEG nanoparticles, this hydrogel system enables sustained KGN release while maintaining injectability, self-healing properties, and a 3D porous architecture. Mechanical characterization revealed superior bioadhesion strength (∼1,150 kPa) and compressive modulus (∼195 kPa). The hydrogel demonstrated excellent biocompatibility, significantly promoting bone marrow mesenchymal stem cells (BMSCs) proliferation, migration, and chondrogenic differentiation in vitro. In vivo evaluations showed superior ICRS and modified O’Driscoll histological scores in defects treated with the KGN-loaded chitosan hydrogels compared to controls. Histological analysis confirmed enriched type II collagen deposition in newly formed cartilage, exhibiting structural organization and integration with host cartilage comparable to natural tissue. This novel KGN-loaded bioadhesive dynamic hydrogel provides an optimized regenerative microenvironment for cartilage repair, demonstrating substantial translational potential for clinical applications.